Performance modelling and validation on co-gasification of coal and sawdust pellet in research-scale downdraft reactor - Mansur, F.Z. (IOP Publishing Ltd, 2019)
Co-gasification of the fossil fuel with the biomass is considered a very promising clean energy opt-in reduce the greenhouse gas emission. The main objective of this research is to develop a simple and reliable model provided as a preliminary tool to evaluate the performance of the co-gasification of sub-bituminous coal with densified biomass (sawdust pellet, SP). The simulation model using Aspen Plus was validated with the experimental data for minimization of the Gibbs free energy model. Three performance parameter; the calorific value of the syngas (CVsyngas), syngas yield (Ysyngas) and gasification efficiency (GE) were studied along with three different control parameter. The increase of the sawdust pellet blending ratio denoted in a decrease of the CVsyngas, Ysyngas and Î·GE ranged from 3.00-6.00 MJ/Nm3, 1.20-2.20 Nm3/kg and 25-37, respectively. On the contrary, effect of the gasification temperature at the various blending ratio exhibits an increase for all the performance parameters. In addition, ERair resulted in the decline of the CVsyngas from 8.50 to 1.58 MJ/Nm3 and Î·GE from 52 to 15 while vice versa for Ysyngas. Furthermore, it is found that the result obtained from the developed model agrees well with the experimental data that have been conducted in replicate. Â© Published under licence by IOP Publishing Ltd.